Ajaran Agama Hindu dalam Peningkatan Kerukunan Rumah Tangga Menuju Keharmonisan Hidup - Ni Wayan Gateri (UHN IGB Sugriwa Denpasar, 2016)
Harmony is a dream for every household that are nurtured with love, compassion, and sincerity. In improving household harmony a grounding Hindu religion as guidance is needed. Household harmony is a state of peace, good, friendly, united hearts, agreement that occur in a family life with overcome differences of opinion and differences of understanding. The increase in household harmony creates a peaceful family circumstances that shows happy, life without violence, as well as inner and outer prosperous which are based on realizing the teachings of truth and religion.